The Potential Of Bioactive Compounds Of Moringa oleifera Leaves as α-Glucosidase Inhibitor Reveals Antidiabetic Activity - Ayu Tri Agustin; Nabila Al Unaizah; Lulut Sasmito; Mohammad Rofik Usman (LPPM Universitas dr. Soebandi, 2025)
Type 2 diabetes mellitus is the most common type of diabetes, accounting for approximately 90% of all diabetes cases. The enzyme α-glucosidase is an important therapeutic target due to its role in breaking down carbohydrates into glucose in the small intestine. Moringa leaves (Moringa oleifera) are known to have antihyperglycemic effects through the inhibition of this enzyme, making the active compounds within them a potential natural antidiabetic agent. This study aims to evaluate the physicochemical profile, pharmacokinetics, and bioactivity of six compounds in moringa leaves (4-Undecylbenzenesulfonic acid, Apigetrin, Quercetin-3-β-D-glucoside, D-(-) -Quinic acid, Corchorifatty acid F, and 4-Hydroxybenzaldehyde) using in silico methods, with Voglibose as a control, against the α-glucosidase receptor (PDB ID: 5KZX) via the Hex 8.0.0, PyRx 0.8, and BIOVIA Discovery Studio 2019 applications. The results showed that four compounds (Apigetrin, D-(-)Quinic acid, Corchorifatty acid F, and 4-Hydroxybenzaldehyde) met Lipinski's rules and had good pharmacokinetic profiles. In terms of bioactivity, Apigetrin and D-(-)Quinic acid had Pa values >0.5, indicating potential as antidiabetic agents. Docking analysis revealed that all compounds could interact with α-glucosidase, but their binding energies were still higher than Voglibose (-1425.3 kcal/mol). Among the tested compounds, Apigetrin showed the lowest value (-334.1 kcal/mol). This study suggests that Apigetrin, D-(-)-Quinic acid, Corchorifatty acid F, and 4-Hydroxybenzaldehyde may have potential as candidates for type 2 antidiabetic drugs due to their α-glucosidase inhibitory properties. Based on the binding energy of the compounds found in moringa leaves, they bind outside the active site of the ligand.